Neurofilament Light Chain Protein Is a Predictive Biomarker for Stroke After Surgical Repair for Acute Type A Aortic Dissection - Zhang, Kai; Wang, Zhu; Zhu, Kai; Dong, Songbo; Pan, Xudong; Sun, Lizhong; Li, Qing (Frontiers in Cardiovascular Medicine, 2021)
Background: Although great progress has been made in surgery and perioperative care, stroke is still a fatal complication of acute type A aortic dissection. Serum biomarkers may help assess brain damage and predict patient’s prognosis. Methods: From March, 2019 to January, 2020, a total of 88 patients underwent surgical treatment at the Department of Cardiovascular Surgery of Beijing Anzhen Hospital, China, and were enrolled in this study. Patients were divided into two groups according to whether they had suffered a stroke after the operation. Blood samples were collected at 8 time points within 3 days after surgery to determine the level of S100β, neuron-specific enolase (NSE) and neurofilament light chain protein (NFL). Receiver operating characteristic curves (ROC) were established to explore the biomarker predictive value in stroke. The area under the curve (AUC) was used to quantify the ROC curve. Results: The patient average age was 48.1 ± 11.0 years old and 70 (79.6%) patients were male. Fifteen (17.0%) patients suffered stroke after surgery. The NFL levels of patients in the stroke group at 12h and 24h after surgery were significantly higher than those in the non-stroke group (all P<0.001). However, the NSE and S100β levels did not differ significantly at any time point between the two groups. The predictive value of NFL was the highest at 12h and 24h after surgery, and the AUC was 0.834 (95% CI, 0.723-0.951, P<0.001) and 0.748 (95% CI, 0.603-0.894, P=0.004), respectively. Its sensitivity and specificity at 12h were 86.7% and 71.6%, respectively. The NFL cutoff value for the diagnosis of stroke at 12h after surgery was 16.042 ng/ml. Conclusions: This study suggests that NFL is an early and sensitive serum marker for predicting postoperative neurological prognosis of ATAAD patients. Further studies, including large-scale prospective clinical trials, are necessary to test whether the NFL can be used as a biomarker for clinical decision-making.